Recognition of non-drilled polar codes based on soft decision - Zhaojun WU; Zhaogen ZHONG; Limin ZHANG; Bo DAN (Tongxin xuebao)
In order to solve the problem of the blind recognition of polar codes, the theorem 1 and theorem 2 were proved firstly, which reflects the relationship between length and rate of actual polar codes, and then theorem 3 which could distinguish frozen bit and information bit positions was also proved.Based on these three theorems, the codewords matrixes and Kronecker matrixes were constructed by traversing the possible code length values.Then the information bits were traversed to detect the check relationship between the codewords and the suspected dual space.In order to detect the check relationship, log likelihood ratio was introduced, based on its characteristics and optimal criteria, the code rate and information bit positions were estimated.The simulation results show that the conclusions of the three theorems are consistent with the results.At the same time, the proposed algorithm has a strong error tolerance.Under 6.5 dB and code length of 1024, the rate of recognition can reach more than 98%.